2022
DOI: 10.1177/16094069221139474
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Coding in Multi-National Teams: Benefits, Challenges and Experiences Promoting Equitable Research

Abstract: Within multi-national research collaborations, power dynamics often shape who is involved in which parts of the research process. The analysis phase of research has historically been framed as requiring expert perspective, excluding national or local researchers whose role is often limited to collecting data and transferring it to others to analyze. In this paper, we describe and reflect on the process of collaborative coding across a multi-national team based in Lebanon and the United Kingdom, as part of a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…We used deductive and inductive coding, meeting bilaterally in pairs and regularly in a group to discuss codes and share perspectives on the data. The process of collaborative coding is described in more detail elsewhere [ 31 ]. While Gaventa’s power cube and Arnstein’s ladder of participation influenced the development of topic guides, during analysis, we found that participant accounts closely matched Arnstein’s ladder but did not neatly map onto the power cube.…”
Section: Methodsmentioning
confidence: 99%
“…We used deductive and inductive coding, meeting bilaterally in pairs and regularly in a group to discuss codes and share perspectives on the data. The process of collaborative coding is described in more detail elsewhere [ 31 ]. While Gaventa’s power cube and Arnstein’s ladder of participation influenced the development of topic guides, during analysis, we found that participant accounts closely matched Arnstein’s ladder but did not neatly map onto the power cube.…”
Section: Methodsmentioning
confidence: 99%
“…Interviews with service users and caregivers adopted a narrative approach, in which the participant is asked to tell their story of navigating and accessing the services, with subsequent probes as needed to explore health care seeking and financing in relation to MH services. Narrative interviewing gives the participant control over how they share their stories, allowing a relaxed and unstructured approach that can elicit depth and, at times, more accurate information than obtained in a structured interview [ 47 , 48 ]. This contributes to dismantling power hierarchies linking the researcher and participant [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dedoose software was used for coding the data. Six Authors (NSS, REM, JE, BM, RA, SC) coded the data in pairs and used collaborative coding approach [ 48 ] to analyse, define and refine the codes where they held group meetings for that purpose. During these meetings, each pairs’ coding was checked with the team of authors and key themes of each transcripts were identified and discussed collaboratively.…”
Section: Methodsmentioning
confidence: 99%